A reaper at the gates - Tahir, Sabaa (Tahir, Sabaa. Ember in the ashes, 2018)
Beyond the Empire and within it, the threat of war looms ever larger as the Blood Shrike, Helene Aquilla, Laia of Serra, and Elias Veturius all face increasing dangers.